Pengaruh Current Ratio, Debt To Equity Ratio Dan Inventory Turnover Terhadap Profitabilitas Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Di Bei Periode 2018-2021 - Ali Muhdor (Universitas 45 Surabaya, 2023)
This study aims to determine the effect of current ratio, debt to equity ratio and inventory turnover on profitability in food and beverage sub-sector manufacturing companies listed on the IDX for the 2018-2021 period. This research is a quantitative research. The population in this study is food and beverage sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021. The sample in this study was 21 companies through certain considerations. Data collection techniques using financial statement data. The data analysis technique uses multiple linear regression. The results of this study show that 1) the Current Ratio variable partially has no effect on profitability in food and beverage sub-sector manufacturing companies listed on the IDX for the 2018-2021 period. 2) The variable Debt to Equity Ratio partially affects the profitability of food and beverage sub-sector manufacturing companies listed on the IDX for the 2018-2021 period. 3) Variable Inventory Turnover partially does not affect profitability in food and beverage sub-sector manufacturing companies listed on the IDX for the 2018-2021 period. The results of the coefficient of determination show that the variables current ratio, debt to equity ratio and inventory turnover are able to contribute to the company's profitability by 53.8%